Synthesis and characterization of a heterobimetallic Cu–Zr complex for deposition of 1:1 CuZrO3–CuO composite thin films. (25th September 2015) - Ehsan, Muhammad Ali; Khaledi, Hamid; Arifin, Zainudin; Mazhar, Muhammad
Graphical abstract: The heterobimetallic complex [Cu4 Zr2 ( μ 4 -O)2 (dmae)4 (OAc)8 ]·2H2 O has been synthesized, structurally characterized and utilized as a single source precursor in the aerosol assisted chemical vapor deposition technique to deposit CuZrO3 –CuO composite oxide thin films on a soda glass substrate in air atmosphere at temperature of 575 °C. Abstract: A well-defined heterobimetallic complex, [Cu4 Zr2 ( μ 4 -O)2 (dmae)4 (OAc)8 ]·2H2 O1 where dmae = N, N -dimethylaminoethanolato and OAc = acetato, has been constructed by the chemical reaction of Cu(OAc)2 ·2H2 O with Zr(dmae)4 in THF. Complex1 was characterized by its melting point, elemental analysis, infrared spectroscopy, thermogravimetric analysis and single crystal X-ray diffraction. X-ray crystallography shows that complex1 crystallizes in the monoclinic space group P 21/ n with the cell dimensions a = 14.7414(5), b = 11.7378(4) and c = 14.8196(5) Å and β = 94.826(2)°. The nature of the thermolysis of1 showed its aptitude to give a 1:1 CuZrO3 :CuO composite oxide material at 575 °C. The high solubility and stability of1 in common organic solvents suggest its efficacy as a single source precursor (SSP) in the aerosol assisted chemical vapor deposition technique for the formation of a CuZrO3 –CuO composite thin film on a soda lime glass substrate under an air atmosphere. Thin film properties, such as crystallinity, identification of deposited phases, surface morphology and chemical compositions were probed by X-ray diffraction, scanning electron microscopy and energy dispersive X-ray analysis, which ascertained the evolution of good quality crystalline hemispherical architecture composite oxide thin films from1 .